Three new species of the parasitic wasps genus Spilomicrus Westwood (Hymenoptera: Diapriidae) from the East Palaearctic Region - Chemyreva, Vasilisa G. (Zootaxa, 2015)
Three new species of Spilomicrus Westwood from the East Palaearctic with occipital flange broad and notauli broad and deep posteriorly, S. notaulus sp. nov., S. nottoni sp. nov. and S. lubomasneri sp. nov., are described, illustrated and keyed. Variation of the character states, distribution and comparative diagnosis of each species are provided.